Social-Economic Factors, Student Factors, Student Academic Goals and Performance of Students in Institutions of Higher Learning in Uganda - Ngoma, Muhammed; Ntale, Peter Dithan; Abaho, Earnest (Africa Education Review, 2017)
This article evaluates the relationship between social-economic factors, students’ factors, student academic goals and performance of students. The study adopts a cross-sectional survey, with largely quantitative approaches. A sample of 950 students was randomly and proportionately drawn from undergraduates in four institutions of higher learning. A response rate of 61% was recorded. We observed significant positive relationships between student factors (except competence in quantitative subjects and grades earned in high school) and student performance, as well as student learning goals and student academic performance. We did not observe a significant relationship between socio-economic factors and student performance at higher institutions. The model was significant, and explained 47% of the variation in student performance. The study recommends that higher institutions should place considerable emphasis on inculcating a reading/preparation culture among students, enforce attendance at lectures and encourage students to set learning goals, if they are to improve the performance of their students.
Keywords: Social-economic factors; Student factors; Student academic goals; Student performance